PENGARUH MASSAGE PUNGGUNG TERHADAP PENURUNAN NYERI PERSALINAN KALA I FASE AKTIF DAN KECEPATAN PEMBUKAAN PADA IBU BERSALIN DI BPS AL-HIKMAH JABON MOJOKERTO - RAHMAWATI, IMA; LESTARI, INDAH (JURNAL KEPERAWATAN BINA SEHAT, 2014)
The process of childbirth is a natural cycle in a woman. Similarly, the pain during childbirth. Pain occurs due to contraction during the process of opening and thinning of the cervix. Increasing the frequency and duration of the contractions more intense pain is felt especially in primigravida mothers. This study aims to analyze the influence of the Deep Massage to the decrease of labor pain when active phase and the speed of the opening in the mother giving birth in the working area of BPS Al-Hikmah Mojokerto district.The study was true experimental design